A study of mitochondrial A1555G mutation in aminogl ycoside induced ototoxicity - Eshamsol Kamar, Omar (2008)
Aminoglycoside induced ototoxicity is one of the most common causes of acquired deafness, involving the auditory and vestibular system. The Vestibular and Audiotoxicity is frequently irreversible. In developing countries, eg Malaysia, aminoglycoside are more routinely used even for a minor infection, since it is relatively cheap and easily available. However, studies conducted in Asian country had proved that aminoglycoside caused 10 to 20% of hearing loss. (mitochondrial A 15550 Mutation - An alteration or change, as in nature, form, or quality of a gene that maternally inherited gene during fetal life and has an association with hearing loss). People who carry the genetic mutation of mitochondrial DNA (mtDNA) A 15550, has a higher risk of having hearing loss when expose to aminoglycoside drug (eg: streptomycin, gentamycin etc) compare to them who do not carry the mutation gene. A study which was conducted in Japan, found that 40% of the patient who had hearing loss due to this drugs, also carry the mtDNA A1555G mutation. From this study, we hope that we can detect early genetic Al555G mutation, especially in newborn baby, so that prevention can be made early and precaution should be taken before prescribing amino glycoside drugs. Objectives: The purpose of this study is to determine the prevalence and association of mtDNA A1555G mutation in subjects with aminoglycoside-induced ototoxicity. Methodology: A cross sectional study was carried out in Otorhinolaryngology clinic HUSM and PKB, Kota Bharu from June 2007 to May 2008. Twenty two subjects with aminoglycoside induced ototoxicity and twenty two control subjects without ototoxicity after exposed to aminoglycosides were included in this study. Ototoxicity was confirmed by pure tone audiometry and distortion product otoacoustic emission (DPOAE). All eligible and consented patient was underwent buccal mucosa swab for further genetic analysis for mtDNA A 15550 mutation. Results: There was I subject (4.54%) in the aminoglycoside-induced ototoxicity group identified to have the mtDNA A 15550 mutation. There was no significant association between mtDNA Al555G mutation and ototoxicity in this study (P = 0.500). Conclusion: In our study, we found mtDNA Al555G mutation in one of our subject who had hearing loss secondary to ototoxic drug. Though, it was not significant statistically. There is a possibility that the prevalence of this mtDNA mutation is truly very low in our population. However, a further larger study with a bigger sample size and a wider area of coverage need to be done to confirm our finding.